Understanding Customer Purchase Style Effect On Customer Satisfaction And Purchase Intention Toward Plant-Based Burgers - Wellem Ghori Wondiwoy; Eddy Yansen (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The main objective of this study is to examine the effect of customer purchase style, satisfaction, and purchase intention toward plant-based burgers. Second, to find out the effect of customer satisfaction and purchase intention among Non-Vegetarian in the city of Jakarta, Indonesia. This study uses a mixed approach (qualitative and quantitative. The data was gathered from 20 interviewed participants and 205 respondents of non-vegetarian customers of plant-based burgers in Jakarta. The qualitative data analysis was carried out using NVIVO 12 Pro, while the quantitative data analysis was carried out using Structural Equation Model – partial Least Square (SEM-PLS) using SmartPLS3. The Results of qualitative analysis find that the informants were perceived positively or impressed with plant-based burgers in terms of achievement, value and idea. The result of quantitative analysis shows that customer purchase style (hedonic and utilitarian) has a positive and significant effect among non-vegetarian customers in Jakarta. Customer purchase style (hedonic and utilitarian) has a positive and significant effect on purchase intention among non-vegetarian customers in Jakarta. Customer purchase style (hedonic and utilitarian) has a positive and significant effect on customer satisfaction among non-vegetarian customers in Jakarta. Customer satisfaction has a positive and significant effect among non-vegetarian customers in Jakarta. Customer satisfaction has a positive and significant effect on purchase intention among non-vegetarian customers in Jakarta. Though it was not hypothesized, Customer satisfaction mediates the effect of customer purchase style among non-vegetarian customers in Jakarta. Finally, customer satisfaction mediates the effect of customer purchase style on purchase intention among non- vegetarian customers in Jakarta